PENGARUH PENGELOLAAN KELAS TERHADAP DISIPLIN BELAJAR SISWA KELAS V SD NEGERI SERDANG WETAN - Nur'aini, Nadila; Mujazi Mujazi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of classroom management on the learning discipline of fifth-grade students at SD Negeri Serdang Wetan. This is a quantitative study using a survey method. The population in this study consists of all 120 fifth-grade students, with a sample size of 89 students. Data collection techniques in this study used questionnaires (surveys). The information obtained from the respondents using this questionnaire was used to determine the effect of classroom management on learning discipline. This study used a partial test (t-test) to determine the hypothesis. The results obtained based on the partial test (t-test) were 4.529 t-calculated > 1.663 t-table with a significance of 0.00<0.05. These results indicate that H0 is rejected and H1 is accepted, meaning that there is a partial influence between Classroom Management (X) and Learning Discipline (Y). The results of the R Square test or coefficient of determination show that the partial influence of the classroom management variable on learning discipline is 19.1%. This result indicates that classroom management plays an important role in supporting the formation of learning discipline, although it is not the only determining factor. This study is useful as a consideration for teachers and schools in improving learning discipline through more effective classroom management strategies. The limitation of this study lies in the low percentage of contribution, so further research is expected to add other variables such as motivation, family role, and social environment.